The Illusion of Sovereignty or State-Making Devices of The Globalizing World - V. V. Subochev (MGIMO University Press, 2019)
Review of a monograph: Guy Fiti Sinclair. To Reform the World: International Organizations and the Making of Modern States. Oxford: Oxford University Press, 2017. 368 p.The book by Guy Fiti Sinclair is a highly professional and richly contextualized scientific research which analyzes the processes of expansion of powers exercised by international organizations under international law. Particular attention is devoted to the reasons which made this expansion possible and legitimate.Sinclair views international organizations as the creatures, instruments and even originators of international law which incarnated and epitomized its transformative potential for the purposes of their expansion and development. Heterogeneous interests and ambiguous functions of the International Labour Organization, the UN, and the World Bank are inspected through the prism of their abilities to intervene in the name of international law and, at the same time, to subject themselves to its improving and modernizing influence.The reviewed work comprehensively explores the state-making activities of full-fledged democracies and the ambivalent consequences of such modernization which usually deploys under the guise of transformative liberal ideology.